Studi Komparasi Kuat Tekan dan Kuat Tarik Beton Self-Compacting Concrete dengan Substitusi Fly Ash dan Silica Fume - Anandha Risal Ariyanto; Ahmad Nur Syariffudin; Antonius, Antonius (Journal of Engineering and Applied Technology, 2026)
Self-Compacting Concrete (SCC) is an innovative concrete that can flow and compact itself without a compactor, making it highly effective for use in structures with dense reinforcement and complex shapes. However, the high cement requirements of SCC increase costs and carbon emissions, necessitating alternatives in the form of pozzolanic material substitutions such as fly ash and silica fume. This study aimed to analyze the effect of these two materials on the compressive and splitting tensile strength of SCC concrete through experimental methods with substitution variations of 0%, 10%, and 15% of the cement weight, as well as testing of fresh properties according to standards. The results showed that pozzolanic material substitution improved the mechanical performance of SCC, but to varying degrees. The addition of 10% fly ash only provided a moderate increase in compressive strength of approximately 4% at 28 days and had no significant effect on splitting tensile strength. On the other hand, 10% silica fume proved to be the most optimal composition because it produced the highest compressive strength of 57.49 MPa (an increase of about 28% from normal concrete) and increased the splitting tensile strength to 3.58 MPa, making it more effective for high-quality SCC.